2018
DOI: 10.1177/0300060518759892
|View full text |Cite
|
Sign up to set email alerts
|

Hepatopulmonary fusion associated with right-sided congenital diaphragmatic hernia: management of this rare anomaly and a review of the literature

Abstract: Hepatopulmonary fusion is a rare malformation that is often discovered during operative repair of right-sided congenital diaphragmatic defects. Based on a search using medical search engines, we only found 22 cases of hepatopulmonary fusion in the English literature worldwide to date. We describe herein a case of hepatopulmonary fusion with right-sided congenital diaphragmatic hernia in a female neonate who presented with respiratory distress. We discuss management of this case and review the relevant literatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 25 publications
(43 reference statements)
1
13
0
Order By: Relevance
“…Patients often die in the perioperative period due to respiratory failure, pulmonary hypertension, right heart failure, congenital heart diseases, and thrombosis of the inferior vena cava. 30 In this review, the survival rate among the cases reported in literature was 58.8 and 50% in the report of the CDG Study Group. The overall survival was 56.8%.…”
Section: Prognosismentioning
confidence: 70%
See 3 more Smart Citations
“…Patients often die in the perioperative period due to respiratory failure, pulmonary hypertension, right heart failure, congenital heart diseases, and thrombosis of the inferior vena cava. 30 In this review, the survival rate among the cases reported in literature was 58.8 and 50% in the report of the CDG Study Group. The overall survival was 56.8%.…”
Section: Prognosismentioning
confidence: 70%
“…The demonstration of hepatic veins draining directly into the right atrium also suggests HPF. 30 Whenever there is a right CDH with mediastinum deviation to the right, an advanced imaging study should be conducted to exclude HPF. A routine ultrasound with color Doppler should be performed in all cases of right CDH.…”
Section: Clinical Presentationmentioning
confidence: 99%
See 2 more Smart Citations
“…8 In a review of literature, the combination of right CDH, HPF, and anomalous venous drainage of the right lung was reported in one case, 9 and the association of HPF and sequestration was reported in 3 cases. 10 However, the association of bilateral CDH, HPF, partial anomalous right pulmonary venous drainage and sequestrated lobe was not reported before.…”
Section: Follow-up and The Outcomesmentioning
confidence: 93%